2014
DOI: 10.1016/j.jim.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria toxin-based bivalent human IL-2 fusion toxin with improved efficacy for targeting human CD25+ cells

Abstract: Regulatory T cells (Treg) constitute a major inhibitory cell population which suppresses immune responses. Thus, Treg have proven to be key players in the induction of transplantation tolerance, protection from autoimmune disease and prevention of the development of effective anti-tumor immune reactions. Treg express high levels of the high affinity interleukin-2 receptor (IL-2R) consisting of IL-2Rα (CD25) together with IL-2Rβ (CD122) and the common γ-chain (CD132). An effective reagent capable of depleting T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…With this expression system, the expressed human IL-2 fusion toxins were secreted into the culture medium which facilitated the down-stream purification. The production level and quality were significantly improved comparing with the Ontak ® -production system E.coli (Peraino et al, 2014). In vitro efficacy analysis demonstrated that both monovalent and bivalent human IL-2 fusion toxins were potent and the bivalent isoform is approximately two logs more potent than the monovalent isoform using human CD25 + HUT102/6TG cells (Peraino et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With this expression system, the expressed human IL-2 fusion toxins were secreted into the culture medium which facilitated the down-stream purification. The production level and quality were significantly improved comparing with the Ontak ® -production system E.coli (Peraino et al, 2014). In vitro efficacy analysis demonstrated that both monovalent and bivalent human IL-2 fusion toxins were potent and the bivalent isoform is approximately two logs more potent than the monovalent isoform using human CD25 + HUT102/6TG cells (Peraino et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…1, Peraino et al, 2014). With this expression system, the expressed human IL-2 fusion toxins were secreted into the culture medium which facilitated the down-stream purification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Denileukin diftitox, a diphtheria toxin fragment IL-2 fusion protein, targets and kills CD25 ( + ) cells 19 Recently, a newly constructed diphtheria toxin DT 390 porcine IL-2 truncated fusion toxin (Bi-NonGly) has also shown great potential for in vivo depletion of porcine CD25 + cells. 20 Bivalent human IL-2 fusion toxin has proved to be more potent than the current, clinically-used monovalent fusion toxin (denileukin diftitox, Ontak®) for in vivo depletion of Treg cells 2124 .…”
Section: Introductionmentioning
confidence: 99%